Herbicide trials in carrots - Zanon, Ayrton; Nísio, Jair (Pesquisa Agropecuaria Brasileira, 2014)
Two carrot herbicide trials were carried out at the Instituto de Pesquisa Agropecuária Meridional, using Herbi Shell n.° 10, Lorox (Linuron), Tok E-25 (Nitrofen) and Tenoran (Chloroxuron). In the first trial all herbicides were applied in pre-emergence treatments, except for Herbi Shell n.° 10 which was applied only in post-emergence. In the second trial the herbicides were applied in post-emergence treatments. Hoed plots were considered as controls. The effectiveness of the herbicides was evaluated based on carrot yields and the total green weight of weeds. Correlation analysis of the results indicated an increase in carrot yield with a decrease in the total green weight of weeds. Except for Lorox which was the most effective in reducing the total green weight of weeds and allowed the best carrot yield in post-emergence treatment, no significant differences were observed among the other chemicals in either trial.